URGENSI PENCEGAHAN STUNTING DI ERA NEW NORMAL: EDUKASI GIZI ANAK DAN PEMBERDAYAAN MASYARAKAT DI DESA KADUDAMPIT KECAMATAN SAKETI KABUPATEN PANDEGLANG - Prafitri, Nikki (Jurnal Pengabdian Dinamika, 2022)
Stunting is a condition in which children are malnourished, characterized by short stature in childrenunder five years old. The new normal era where people are still affected by Covid-19, especially in theeconomic sector can affect the fulfilment of nutrition for children. Pandeglang Regency has succeededin reducing stunting rates during the pandemic. This success needs to be supported by continuouspubliceducationsteps.Serviceactivitiesregardingchildnutritioneducationandcommunityempowerment in preventing stunting are urgent things to prevent the increase in stunting in the newnormal era. The method used in this activity is education to the community through counselling andeducation to the community in Kadudampit Village, Saketi District. The targets of this activity areposyandu cadres, housewives and village youth community. The result of this activity is the target ofactivities to gain new knowledge about child nutrition and community empowerment efforts to preventstunting. Community empowerment is carried out to create an independent community that candisseminate information on child nutrition to prevent stunting and conduct periodic stunting-relatedprograms at the village level. Community empowerment can be done by establishing a child nutritionforum and a child nutrition post community as the first place for the community to consult about childnutrition.